Finance theory and asset pricing - "Milne, Frank" (Oxford, 1995)
This book provides a concise guide to financial asset pricing theory. Assuming a basic knowledge of graduate microeconomic theory, it explores the fundamental ideas that underlie competitive financial asset pricing models with symmetric information. Using finite dimensional techniques, this book avoids sophisticated mathematics and exploits economic theory to clarify the essential structure of recent research in asset pricing. In particular it explores arbitrage pricing models with and without diversification, Martingale pricing methods, representative agent pricing models; discusses these ideas in two date and multi-date models; and provides a range of examples from the literature.
Keywords: Finance - mathematical models